Detection Of Antibiotic Residues in Eggs of Layer Chickens and Knowledge of Animal Officers About Antibiotics - Jefrianda Jefrianda; Nurliana Nurliana; Darmawi Darmawi; Teuku Reza Ferasyi; Sugito Sugito (The Faculty of Veterinary Medicine of Syiah Kuala University, 2021)
The chicken farming industry in Indonesia cannot be separated from the use of antibiotics as a curative effort in controlling the disease. Its use is either via injection, soaking, or as a feed additive (growth promoter) mixed in feed. Inappropriate use of antibiotics causes allergic reactions or resistance and the possibility of causing poisoning, residues in livestock tissues or organs that are harmful to human health when consuming them. This study aimed to determine the antibiotic residues in eggs and the level of knowledge of livestock workers on the use of antibiotics in livestock. The detection of antibiotic residues was conducted using the agar plate diffusion method by Kirby Bauer with the disk diffusion technique using Escherichia coli and Salmonella sp. As indicator bacteria. The results were analysed using a qualitative descriptive approach. The samples were 76 eggs taken from the Regional Technical Implementation Unit of the Non-Ruminant Livestock Center of the Aceh Livestock Service in Blang Bintang and Saree Aceh Besar. Chloramphenicol antibiotic was used as a test medium and as control by calculating the diameter of the inhibition zone formed on MHA media. furthermore, a cross-sectional study design was used and questionnaires were distributed to 14 livestock officers to understand the knowledge of officers on the use of antibiotics in livestock by using google form. The data were analyzed using the chi-square test through the SPSS 22.0 program. The results showed that the eggs and feed samples were negative from antibiotic residue. There was no relationship between feeding and antibiotic residues in eggs and laying hens feed. However, only 35.7% of officers had good knowledge about proper antibiotic usage. This means continuing awareness to the officers regarding the use of antibiotics either for treatment of diseases or as feed promoter are essential.